2018
DOI: 10.1007/s00425-018-2953-3
|View full text |Cite
|
Sign up to set email alerts
|

Spodoptera litura-mediated chemical defense is differentially modulated in older and younger systemic leaves of Solanum lycopersicum

Abstract: Metabolite profiling, biochemical assays, and transcript analysis revealed differential modulation of specific induced defense responses in local, older, and younger systemic leaves in Solanum lycopersicum upon Spodoptera litura herbivory. Plants reconfigure their metabolome upon herbivory to induce production of defense metabolites involved in both direct and indirect defenses against insect herbivores. Herbivory mediated leaf-to-leaf systemic induction pattern of primary and non-volatile secondary metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 82 publications
2
36
0
Order By: Relevance
“…2d). Systemic defense responses are often found to be highly variable in space and time, and many studies have reported differences in local and systemic defense responses to herbivory or exogenous hormone application (Babst et al 2009;Moreira et al 2009;Lee et al 2017;Kundu et al 2018). Systemically induced resistance can be achieved by the systemic transport, through the plant vascular system, of defensive metabolites and/or signals from the induced tissues that activate de novo expression of resistance-associated traits (Heil and Ton 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2d). Systemic defense responses are often found to be highly variable in space and time, and many studies have reported differences in local and systemic defense responses to herbivory or exogenous hormone application (Babst et al 2009;Moreira et al 2009;Lee et al 2017;Kundu et al 2018). Systemically induced resistance can be achieved by the systemic transport, through the plant vascular system, of defensive metabolites and/or signals from the induced tissues that activate de novo expression of resistance-associated traits (Heil and Ton 2008).…”
Section: Discussionmentioning
confidence: 99%
“…is NBAII–MP-NOC-02). After hatching, larvae (50) were reared on gram flour-based artificial diet at 25 ± 2 °C with 8 h /16 h of the light-dark period [ 59 ]. For Arabidopsis fed S. litura, the insects (50) were allowed to feed on 5–6 week old Arabidopsis plants for 24 h prior to gland isolation.…”
Section: Methodsmentioning
confidence: 99%
“…This would provide plants with a mechanism to fine-tune defence responses according to the damaged organ. The observation that systemic responses are stronger than local ones in both roots and shoots suggests that plants invest more resources in preparing distal tissues for efficient defence activation against a potential upcoming attack (Gomez et al, 2010;Steinbrenner et al, 2011;Kundu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%